Pengaruh Work Life Balance dan Self Efficacy terhadap Organizational Citizenship Behavior (OCB) yang Berdampak pada Kinerja Karyawan - Syaipul Amri; Djatmiko Noviantoro; Yusro Hakimah; Yusdiana (Equivalent : Journal of Economic, Accounting and Management, 2024)
Abstract :  The aim of this research is to analyze the influence of work life balance and self efficacy on citizenship behavior (OCB) which has an impact on employee performance. The research method used is a quantitative research method, the population used is 37 people. Researchers used a sampling technique, namely the census technique or saturated sampling. Data collection can use primary sources and secondary sources, where primary data is obtained through questionnaires, documentation and observation. Meanwhile, secondary data was obtained by researchers in the form of history, profiles and HR data of PT employees. Tri Pakarta Insurance, Palembang Branch. The results of the study show that there is an effect of Work Life Balance and Self Efficacy on Organizational Citizenship Behavior (OCB) which have an impact on PT. Tri Pakarta Insurance Palembang Branch, with the equation Y = 0.407X1 + 0.334X2 + ɛ1, and the equation Z = 0.343X1 + 0.264X2 + 0.329Y + ɛ2, there is an effect of work life balance on OCB employees of PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.407 with a T-Statistic value of 2.641 ≥ 1.96, the P-Value is 0.009 ≤ 0.05, there is an influence of self-efficacy on OCB employees of PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.334 with a T-Statistic value of 2.230 ≥ 1.96, the P-Value is 0.026 ≤ 0.05, there is an influence of work life balance on the performance of employees of PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.343 with a T-Statistic value of 2.741 ≥ 1.96, the P-Value is 0.006 ≤ 0.05, there is the influence of self-efficacy on OCB employees of PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.334 with a T-Statistic value of 2.230 ≥ 1.96, the P-Value is 0.026 ≤ 0.05, there is an influence of work life balance on the performance of employees of PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.343 with a T-Statistic value of 2.741 ≥  1.96, the P-Value is 0.006 ≤ 0.05, there is an effect of self-efficacy on the performance of employees of PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.264 with a T-Statistic value of 2.229 ≥ 1.96, the P-Value is 0.026 ≤ 0.05, there is an influence of OCB on the performance of employees of PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.329 with a T-Statistic value of 2.127 ≥ 1.96, the P-Value is 0.034 ≤ 0.05, there is an indirect effect of work life balance on OCB which has an impact on PT Employee Performance . Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.357 with a T-Statistic value of 2.559 ≥ 1.96, the P-Value is 0.011 > 0.05, there is an indirect effect of self-efficacy on OCB which has an impact on Employee Performance at PT. Tri Pakarta Insurance Palembang Branch is shown from the Original Sample value of 0.293 with a T-Statistic value of 2.213 ≥ 1.96, the P-Value is 0.027 > 0.05. Abstrak : Tujuan penelitian ini yaitu untuk menganalisis pengaruh work life balance dan self efficacy terhadap citizenship behavior (OCB) yang berdampak pada kinerja karyawan. Metode penelitian yang digunakan adalah metode penelitian kuantitatif, populasi yang digunakan adalah 37 orang. Peneliti menggunakan teknik sampling yaitu teknik sensus atau sampling jenuh. Pengumpulan data dapat menggunakan sumber primer dan sumber sekunder, dimana data primer diperoleh melalui kuisioner, dokumentasi, dan observasi. Sedangkan data sekunder diperoleh peneliti berupa sejarah, profile, dan data sdm karyawan PT. Asuransi Tri Pakarta Cabang Palembang. Hasil Penelitian menunjukkan bahwa terdapat pengaruh Work Life Balance dan Self Efficacy Terhadap Organizational Citizenship Behavior (OCB) yang Berdampak Pada Kinerja Karyawa PT. Asuransi Tri Pakarta Cabang Palembang, dengan dengan persamaan Y = 0,407X1 + 0,334X2 + ɛ1, dan persamaan Z = 0,343X1 + 0,264X2 + 0,329Y  + ɛ2, terdapat pengaruh work life balance terhadap OCB karyawan PT. Asuransi Tri Pakarta Cabang Palembang ditunjukan dari nilai Original Sample sebesar 0,407 dengan nilai T-Statistik sebesar 2,641 ≥ 1,96, nilai P-Value adalah 0,009 ≤ 0,05, terdapat pengaruh self efficacy terhadap OCB karyawan PT. Asuransi Tri Pakarta Cabang Palembang ditunjukan dari nilai Original Sample sebesar 0,334 dengan nilai T-Statistik sebesar 2,230 ≥ 1,96, nilai P-Value adalah 0,026 ≤ 0,05, terdapat pengaruh work life balance terhadap kinerja Karyawan PT. Asuransi Tri Pakarta Cabang Palembang ditunjukan dari nilai Original Sample sebesar 0,343 dengan nilai T-Statistik sebesar 2,741 ≥ 1,96, nilai P-Value adalah 0,006 ≤ 0,05, terdapat pengaruh self efficacy terhadap kinerja karyawan PT. Asuransi Tri Pakarta Cabang Palembang ditunjukan dari nilai Original Sample sebesar 0,264 dengan nilai T-Statistik sebesar 2,229 ≥ 1,96, nilai P-Value adalah 0,026 ≤ 0,05, terdapat pengaruh OCB terhadap kinerja karyawan PT. Asuransi Tri Pakarta Cabang Palembang ditunjukan dari nilai Original Sample sebesar 0,329 dengan nilai T-Statistik sebesar 2,127 ≥ 1,96, nilai P-Value adalah 0,034 ≤ 0,05, terdapat pengaruh tidak langsung work life balance terhadap OCB yang berdampak pada Kinerja Karyawan PT. Asuransi Tri Pakarta Cabang Palembang ditunjukan dari nilai Original Sample sebesar 0,357 dengan nilai T-Statistik sebesar 2,559 ≥ 1,96, nilai P-Value adalah 0,011 > 0,05, terdapat pengaruh tidak langsung self efficacy terhadap OCB yang berdampak pada Kinerja Karyawan PT. Asuransi Tri Pakarta Cabang Palembang ditunjukan dari nilai Original Sample sebesar 0,293 dengan nilai T-Statistik sebesar 2,213 ≥ 1,96, nilai P-Value adalah 0,027 > 0,05.